SISTEM PENDIDIKAN DI PONDOK PESANTREN AL FATAH DESA TEMBORO KECAMATAN KARAS KABUPATEN MAGETAN: Sistem Pendidikan di Pondok Pesantren Al-Fatah - Muhammad Luthvi Al Hasyimi (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
‘Pondok Pesantren’ (Islamic boarding schools) are educational institutions with various and different education system.Therefore, it remains a concern to researches. The ‘Al Fatah’ - Temboro is one of the Islamic boarding schoolsthat is considered different from the majority of Islamic boarding schools. It is because of the Pesantren's affiliation to the “Jama'ah Tabligh” Da'wah movement. This study discusses the Education System in Pondok Pesantren ‘Al Fatah’, Temboro. In sum, this qualitative research concludes that although Pondok Pesantren ‘Al Fatah’, Temboro has an affiliation to the “Jama'ah Tabligh” Da'wah movement, this Pesantren has the same curriculum and learning methods as other Pesantren in general, especially those affiliated with ‘NU’ (Nahdlatul Ulama); however, the Muhasabah learning method is applied in this Pesantren.